The OPTIMALISASI PENDAPATAN AGROINDUSTRI TAHU DAN TEMPE KABO JAYA DI KECAMATAN SANGATTA UTARA KABUPATEN KUTAI TIMUR - Rusmiyati, Rusmiyati; Istikomah, Istikomah; Akbar, Namirah Larinda (Fakultas Pertanian Universitas Mataram, 2023)
This study aims to determine the optimal revenue and income optimization model for UD Bintang Lima Tahu dan Tempe Kabo Jaya in North Sangatta District. This research was conducted from March to May 2022. The data collected method used was interview and direct observation with the owners of UD Bintang Lima Tahu dan Tempe Kabo Jaya as the population as well as respondents. The analytical tool used LINDO Software with the Linear Programming method. The results showed that the revenue optimization model of UD Bintang Lima Tahu dan Tempe Kabo Jaya was by maximizing raw materials, production machine hours and labor hours. In actual conditions, the total production is 3.423 units of tofu/day and 498 units of tempeh/day. Under optimal conditions, it can produce as much as 3.900 tofu/day and 500 tempeh/day. The total income of UD Bintang Lima Tahu dan Tempe Kabo Jaya is Rp 187.260.000,-/month. Total production is 117.000 units of tofu/month and 15.000 units of tempeh/month with an income of Rp 1.555,- from each sale of 1 tofu and an income of Rp 355.- from every sale of 1 tempeh.